Economic sentiment: Disentangling private information from public knowledge - Katja Heinisch; Axel Lindner (Halle Institute for Economic Research (IWH), 2021)
This paper addresses a general problem with the use of surveys as source of information about the state of an economy: Answers to surveys are highly dependent on information that is publicly available, while only additional information that is not already publicly known has the potential to improve a professional forecast. We propose a simple procedure to disentangle the private information of agents from knowledge that is already publicly known for surveys that ask for general as well as for private prospects. Our results reveal the potential of our proposed technique for the usage of European Commissions' consumer surveys for economic forecasting for Germany.
urn:nbn:de:gbv:3:2-144628
Keywords: C83; D12; D82; E37; 330; consumer confidence; private information; public information; survey data